2009
DOI: 10.1080/10428190902856808
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of single agent bevacizumab in patients with relapsed, aggressive non-Hodgkin lymphoma: Southwest oncology group study S0108

Abstract: Purpose In a phase II trial, SWOG S0108, patients with relapsed, aggressive non-Hodgkin lymphoma were treated with single agent bevacizumab. The primary endpoint was 6 month progression free survival (PFS) with secondary endpoints including response rate, toxicity, and laboratory correlative studies. Patients and Methods 52 patients in first or second relapse with diffuse large B-cell or mantle cell lymphoma were enrolled. 45 patients were eligible. Patients were treated with bevacizumab at 10mg/kg every 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 39 publications
3
51
0
1
Order By: Relevance
“…12 Drawing parallels from the extensive literature on solid malignancies, antiangiogenic lymphoma therapy has focused largely on vascular endothelial growth factor (VEGF), which can drive proliferation of both tumor and endothelial cells. 12,13 However, small phase II clinical studies with the anti-VEGF monoclonal antibody bevacizumab have thus far shown equivocal efficacy in aggressive NHL, 14,15 suggesting that non-VEGF angiogenic pathways may be highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…12 Drawing parallels from the extensive literature on solid malignancies, antiangiogenic lymphoma therapy has focused largely on vascular endothelial growth factor (VEGF), which can drive proliferation of both tumor and endothelial cells. 12,13 However, small phase II clinical studies with the anti-VEGF monoclonal antibody bevacizumab have thus far shown equivocal efficacy in aggressive NHL, 14,15 suggesting that non-VEGF angiogenic pathways may be highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Although the objective response rate (ORR) was low (2%, one partial response (PR) in a patient with DLBCL), singleagent activity was not anticipated given its mechanism of action; combination therapy trials were thus deemed appropriate. 15 The anti-CD20 monoclonal antibody rituximab used in combination with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) chemotherapy is standard treatment for DLBCL. [16][17][18][19][20][21][22] However, there is a need to further improve treatment outcomes, as the 2-year PFS rate of a large populationbased analysis of R-CHOP was only 69%.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of plasma angiogenic factors, including VEGF and VCAM, are associated with poor overall survival (OS) and progression-free survival (PFS) in clinical trials and VEGF, and its receptors are frequently expressed in lymphoma specimens by immunohistochemistry or gene expression profiling. [1][2][3][4][5][6] Resistance to chemotherapy has also been correlated with high levels of VEGF expression in non-Hodgkin lymphoma (NHL) and in xenograft models. [7][8][9][10] Treatment with anti-VEGF therapy plus rituximab or chemotherapy yielded superior antitumor responses compared with either therapy alone.…”
Section: Introductionmentioning
confidence: 99%